2019
DOI: 10.29271/jcpsp.2019.11.1034
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides-to-HDLC Ratio as a Marker of Cardiac Disease and Vascular Risk Factors in Adults

Abstract: Objective: To find out correlation of triglycerides-to-HDL cholesterol ratio in elders with cardiac risk factors like obesity, diabetes, and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
3
13
0
Order By: Relevance
“…Since DRG volume was smaller in smokers when compared to non-smokers, and since it is known that smoking causes microvascular damage, it seems likely that damage to the DRG microcirculation is a contributing factor to DRG atrophy in DPN (Tesfaye et al, 2005;Clair et al, 2015). This hypothesis is further supported by the finding of a positive correlation between L5 DRG SI and triglycerides/HDL ratio, since an increase in the latter has been reported to be associated with microvascular pathology (Ain et al, 2019). The correlation of serum triglycerides with both clinical symptom severity and reduced DRG volume is in line with data from clinical studies that have found elevated triglycerides to be a risk factor for nerve damage and increased severity of neuropathic symptoms in DPN.…”
Section: Discussionmentioning
confidence: 82%
“…Since DRG volume was smaller in smokers when compared to non-smokers, and since it is known that smoking causes microvascular damage, it seems likely that damage to the DRG microcirculation is a contributing factor to DRG atrophy in DPN (Tesfaye et al, 2005;Clair et al, 2015). This hypothesis is further supported by the finding of a positive correlation between L5 DRG SI and triglycerides/HDL ratio, since an increase in the latter has been reported to be associated with microvascular pathology (Ain et al, 2019). The correlation of serum triglycerides with both clinical symptom severity and reduced DRG volume is in line with data from clinical studies that have found elevated triglycerides to be a risk factor for nerve damage and increased severity of neuropathic symptoms in DPN.…”
Section: Discussionmentioning
confidence: 82%
“…Our results are consistent with most other studies. [28][29][30] HDL-c was constantly independently and inversely related to the risks of hyperglycemia, hypertension and hyperuricemia. Therefore, an insufficient HDL-c volume in patients with dyslipidemiaassociated diseases became the basis for clinical attempts to treat patients with dyslipidemia by increasing the level of HDL-c.…”
Section: Discussionmentioning
confidence: 99%
“…5 The TG/HDL-c ratio correlates directly with plasma LDL-c levels, type B, 5,8 reported as an independent CVR factor. 5 To identify cardiac and metabolic threats, it is important to use different TG/ HDL-c ratio cutoff points between genders, 5,11 as the HDL-c level is higher in women. 5 Different cutoff values for men and women are, in fact, used in the National Cholesterol Education Program's (NCEP) criteria for metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified associations between the TG/HDL-c ratio and several cardiometabolic risk factors, such as alcohol use, 7 smoking, 8 metabolic syndrome, 23,24 oxidative 25 and inflammatory profiles, 12,25 adverse events, 10,26 various anthropometric parameters, 5,8,9,24,27 dyslipidemias, 12,24,27 HA. 5,8,11 DM, 5,8,11,24,28 insulin resistance, 11,23,28,29 and renal function. 30 In this sense, the cutoff points found represent the CVR well and are therefore good risk markers for the studied population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation